Enhanced Photoactivity of Oxygen-Deficient Anatase TiO2 Sheets with Dominant {001} Facets - Liu, Gang; Yang, Hua Gui; Wang, Xuewen; Cheng, Lina; Lu, Haofeng; Wang, Lianzhou; Lu, Gao Qing (Max); Cheng, Hui-Ming (Journal of physical chemistry. C, 2009)
Constructing photocatalytically favorable surface structure in synthesizing photocatalysts plays an important role in enhancing the photocatalytic activity of semiconductor photocatalysts. In this report, oxygen-deficient anatase TiO2 sheets with dominant {001} facets were synthesized via a facile one-pot hydrothermal route with solid metallic titanium diboride as precursor. In contrast to anatase TiO2 sheets with dominant {001} facets free of oxygen deficiency and surface fluorine, anatase TiO2 sheets with oxygen deficiency and surface fluorine are subject to obvious surface reconstruction as evidenced by two new Raman-active modes at 155 and 171 cm−1 and the weakened B1g mode at 397 cm−1. Further analysis based on X-ray photoelectron spectroscopy (XPS) spectra of Pt 4f and F 1s provided a clear evidence for the greatly strengthened interaction between Pt-loaded and TiO2 matrix as a result of a special electron-transfer process on the reconstructed surface structure of TiO2 with both oxygen deficiency and fluorine. Importantly, the reconstructed surface structure as well as the strengthened interaction between Pt-loaded and TiO2 matrix can substantially enhance the hydrogen evolution rate from photocatalytic water splitting reactions.